2005
DOI: 10.1152/ajpheart.00060.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transmural pressure in rat initial subpleural lymphatics during spontaneous or mechanical ventilation

Abstract: The role played by the mechanical tissue stress in supporting lymph formation and propulsion in thoracic tissues was studied in deeply anesthetized rats (n = 13) during spontaneous breathing or mechanical ventilation. After arterial and venous catheterization and insertion of an intratracheal cannula, fluorescent dextrans were injected intrapleurally to serve as lymphatic markers. After 2 h, the fluorescent intercostal lymphatics were identified, and the hydraulic pressure in lymphatic vessels (P lymph) and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 24 publications
1
91
0
1
Order By: Relevance
“…Lymphatic outflow from the peritoneal cavity has been described as mostly passing through the diaphragmatic stomata and corresponding lymphatic vessels and, therefore, may be dependent on muscular movement of this organ associated with breathing (19,38). Our results indicated that, unlike after subcutaneous injection, some outflow from the peritoneal cavity continued under anesthetized conditions.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Lymphatic outflow from the peritoneal cavity has been described as mostly passing through the diaphragmatic stomata and corresponding lymphatic vessels and, therefore, may be dependent on muscular movement of this organ associated with breathing (19,38). Our results indicated that, unlike after subcutaneous injection, some outflow from the peritoneal cavity continued under anesthetized conditions.…”
Section: Discussionmentioning
confidence: 53%
“…However, similar to the periphery, there was a large increase in the lymphatic transport of tracer to blood when the mice were awake compared with when they were anesthetized. It has previously been reported that respiratory movement is reduced in anesthetized animals lying on their back (38,39). Other investigators have also previously found decreased lymphatic outflow from the peritoneum under anesthesia (40)(41)(42) and have speculated that abdominal muscle tone plays a large role in driving flow out of the peritoneum.…”
Section: Discussionmentioning
confidence: 96%
“…Both spontaneous active (intrinsic) lymphangion contractions and passive (extrinsic) tissue compressive forces cooperate to generate sufficient pressure gradients to propel lymph centrally. [73][74][75][76] To maintain a unidirectional lymph flow, lymphatics can propel lymph by spontaneous phasic contractions as a result of coordinated contractility of the LMC in the wall of collecting lymphatics. 77 Rat and guinea pig studies have shown that the spontaneous phasic contractions of lymphatics are initiated by a pacemaker electrical activity located in each segment near the valves, with the contraction cycles of lymphatics divided into a contraction phase (systolic) and a relaxation phase (diastolic).…”
Section: General Functions Of the Lymphatic Systemmentioning
confidence: 99%
“…Subsequent lymph propulsion relies on the presence of hydraulic pressure gradients developing between two consecutive tracts of the lymphatic vessel, separated by unidirectional intraluminal valves. It has been shown that the pressure gradients necessary for both formation and propulsion of diaphragmatic lymph may result from forces arising in the tissue and transmitted to the vessel lumen during the cardiac (30) and/or respiratory cycle (22). In addition, unlike what was observed in linear vessels of the central tendineous diaphragm, several loops and short linear tracts located at the outer diaphragm muscular periphery display an intrinsic pumping activity.…”
Section: In Diaphragmatic Lymphatics Flow Velocity and Lymph Flow Wementioning
confidence: 99%
“…Being that this is true also for the lung and with the consideration that passive mechanical ventilation without active inspiratory muscle contraction inhibits lymph flow from thoracic tissues (22), maintenance of spontaneous ventilation would be crucial in preventing and/or limiting the occurrence of pulmonary edema.…”
Section: Ajp-heart Circ Physiolmentioning
confidence: 99%